Lifelong Learning in Nepal: Contexts and Prospects - Regmi, Kapil Dev (AMC Journal, 2020)
After the declaration of the Sustainable Development Goal 4: Ensure inclusive and equitable quality education and promote lifelong learning opportunities for all by the UN, many countries have adapted lifelong learning as one of their main goals for meeting their educational needs. However, lifelong learning as an educational policy concept is defined differently in various contexts. With the case of the context of Nepal this paper, which builds on my thesis prepared for Master of Philosophy degree (Regmi,2009), explores some of the fundamental concepts attached with lifelong learning, mainly non-formal and informal modes of learning as key components of lifelong learning.